Overview of Service Quality for Public Bus Services - Norhisham, Shuhairy; Ismail, Amiruddin; Nazri Borhan, Muhamad; Ismail, Norlela (International Journal of Engineering and Technology, 2019)
Service quality for public transport has recently received many complaints from customers. Nowadays public transport commutes passengers to work or any other places. Buses usually give service to people in rural and urban areas. Increase in population may increase the demand for public transport. Problems with schedule, fare, security and others were obtained. The objective of this article is to overview of services quality for public bus services. This review paper focuses on to understand the definition, issue and methodologies in evaluating service quality in public transport especially public bus services. The methodology using to overview in this article is a comparison between definitions about quality services for public bus, comparison of methodology in conducting assessment for quality services and comparison issues been raise about services quality for public bus. As conclusion, even though there are many problems with regarding service quality for public transport, several ways are developed to improve it slightly better than before. Hence, this research articles can help people and create awareness on the importance of service quality of public bus transportation.Â Â